Performance Analysis Of PID And Fuzzy Logic Controller For Unmanned Underwater Vehicle For Depth Control - Mohd Aras, Mohd Shahrieel; Sulaiman, Marizan; Yeoh, Eik Keong; Kasno, Mohammad `Afif; Mohamed Kassim, Anuar; Khamis, Alias (Penerbit Universiti, UTeM, 2017)
This paper presents study and discussion of tuning process for PID and Fuzzy Logic Controller for Unmanned Underwater Vehicle (UUV) system. Autonomous Underwater Vehicle (AUV) is considered as an UUV where it is commonly used for detecting and mapping submerged wrecks, rocks, and obstructions that is hazardous to navigation for commercial and recreational vessels. The controllers will be designed to control motor thrusters of the AUV. The paper generally discusses PID and FLC, and the focus stresses more on FLC. Differences between both tuning processes will be discussed in details in this paper by covering method of conducting tuning process. Through the process, performance of the system can be analyzed and studied. The output of the system can be tuned or adjusted to a desired and satisfactory level using both of the methods mentioned. For FLCs, tuning process will be a trial-and-error, by making changes to the mapping of membership functions and fuzzy inference rules whereby PID, tuning can be made to the parameter values of the system.